An Investigation on Breast Cancer Knowledge in Developing Nations - Kagita, Usha Sri (International Journal of Indigenous Herbs and Drugs, 2024)
The most common malignant tumor in women diagnosed globally, breast cancer is the leading cause of cancer-related death. Globally, the prevalence of breast cancer is continuously increasing. Breast cancer is the most prevalent type of cancer in the world. Hereditary and genetic predispositions are among the risk factors linked to the incidence of breast cancer. Breast cancers come in a wide variety of forms. The molecular characteristics of breast cancer, including hormone receptor activation (PR, ER, and HER2) and human epidermal growth factor receptor 2 (HER2), genetic changes (BRCA1/2 and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha [PIK3CA] mutations), and immune system markers (PD L1, tumour-infiltrating lymphocytes [TIL], and programmed death-ligand 1 [PD L1]) may impact treatment approaches.